A caring approach to the first-year university student experience - Leonard, Jessica; Mylonas, Aliisa; Parker, Polly; Wood, Rebecca (Journal of University Teaching and Learning Practice, 2024)
This paper presents a case study of a revised approach towards orientation and welcome for commencing students at a research-intensive university in Australia. First-year students, at undergraduate and postgraduate levels, face a range of challenges during their transition to university. This paper describes how we have translated research into practice by taking an evidence-based approach, designed in collaboration with students, and informed by three key aspects in student experience literature: engaging students, building an inclusive community, and fostering a sense of belonging. The approach is informed by key principles of care ethics theory, highlighting the importance of care as a concept in the design of first-year experience initiatives.  The case study includes quantitative and qualitative data from admission and attendance rates and a student survey (n=1052). Student survey data is analysed through a reflexive thematic analysis approach using both inductive and deductive coding. The findings and discussion outline the key success outcomes of the approach both in relation to engagement, community, and sense of belonging and how these contribute towards supporting first-year student transition. Areas for future research are suggested.